2018
DOI: 10.1108/ejm-10-2016-0576
|View full text |Cite
|
Sign up to set email alerts
|

Blinds up or down?

Abstract: Blinds up or down? The influence of transparency, future orientation, and CSR on sustainable and responsible behavior Purpose: One of the critical goals of this research is to explore how and when a business' transparency leads to greater willingness to engage in sustainable and responsible consumption by consumers.Design/methodology/approach: Data were collected in two studies. Study 1 collected data from 219 consumers in a large shopping mall. Study 2 followed an experimental approach and employed data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 108 publications
(240 reference statements)
0
15
0
Order By: Relevance
“…In this context, the concept of sustainability can be referred to as any one of the three dimensions, not only to ecological resources but also to social or economic resources. Sustainability mainly focuses on meeting the needs of the present without compromising the needs of the future [67]. Other researchers have argued that sustainability increases productivity at lower cost and increases business ability [68][69][70].…”
Section: Operational Sustainability (Ops) and Firm Performance (Fpr)mentioning
confidence: 99%
“…In this context, the concept of sustainability can be referred to as any one of the three dimensions, not only to ecological resources but also to social or economic resources. Sustainability mainly focuses on meeting the needs of the present without compromising the needs of the future [67]. Other researchers have argued that sustainability increases productivity at lower cost and increases business ability [68][69][70].…”
Section: Operational Sustainability (Ops) and Firm Performance (Fpr)mentioning
confidence: 99%
“…Ertz and colleagues found a positive difference between enthusiasts and regular consumers on composting, sustainable transportation, and citizen consumption, buta negative difference on recycling; meanwhile, they found no significant difference on local consumption, the environment, or animal protection. Recent studies demonstrate that consumers' willingness to engage in responsible (or sustainable) consumption is impacted by firms' transparency (Foscht et al, 2018). Schlaile et al (2018) conceptualized 'consumer social responsibility' and identified obstacles to responsible consumption.…”
Section: Socially Responsible Consumptionmentioning
confidence: 99%
“…If the crisis intensifies and inventory levels begin to drop, the transparency could cause consumers who already possess sufficient supplies of critical goods to leave them for other customers. Such an approach may be effective as consumers' willingness to engage in responsible consumption is impacted by an organization's transparency (Foscht et al, 2018).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…We also wonder whether enhanced transparency as part of online learning may reduce students' stress and increase their willingness to engage in online learning tools. Prior work has shown that transparency of organizations is associated with greater levels of trust and people's willingness to engage in open and responsible behaviors themselves when they see other relationship partners (eg, organizations) acting in a transparent way [42][43][44][45]. Furthermore, sharing critical information through customer education [45][46][47][48] has been demonstrated to positively affect people's willingness to participate and offer critical and valuable feedback [49][50][51].…”
Section: Limitations and Future Researchmentioning
confidence: 99%